Peran Kompetensi Sumber Daya Manusia dalam Mempengaruhi Determinan Kualitas Laporan Keuangan Pemerintah Daerah - Dreksi, Een; Sartika, Dewi; Maulina, Rina; Mahdani, Said (Politeknik Negeri Medan, 2025)
This research aims to analyze the influence of the internal control system and the use of information technology on the quality of the South Aceh regional government's financial reports, with human resource competency as a moderating variable. The population in this study were all Regional Apparatus Organizations (OPD’s) in South Aceh Regency totaling 56 OPDs. Sample selection used a simple random sampling method, and a final sample of 36 OPDs was obtained. The results of the research show that the Internal Control System has a significant effect on the quality of the financial reports of the Regional Government of South Aceh Regency, while the use of information technology does not show a significant effect on the quality of these financial reports. Human resource competency does not moderate the relationship between the internal control system and the quality of the financial reports of the Regional Government of South Aceh Regency. Human resource competency is able to moderate the relationship between the use of Information Technology and the Quality of Financial Reports of the Regional Government of South Aceh Regency. Abstrak Penelitian ini bertujuan untuk menganalisis pengaruh sistem pengendalian intern dan pemanfaatan teknologi informasi terhadap kualitas laporan keuangan pemerintah daerah Aceh Selatan, dengan kompetensi sumber daya manusia sebagai variabel moderasi. Populasi pada penelitian ini adalah seluruh Organisasi Perangkat Daerah (OPD) yang ada di Kabupaten Aceh Selatan sebanyak 56 OPD. Pemilihan sampel dengan menggunakan metode simple random sampling, dan diperoleh sampel akhir sebanyak 36 OPD. Hasil penelitian menunjukkan bahwa, Sistem Pengendalian Intern berpengaruh signifikan terhadap kualitas laporan keuangan Pemerintah Daerah Kabupaten Aceh Selatan, sementara pemanfaatan teknologi informasi tidak menunjukkan pengaruh signifikan terhadap kualitas laporan keuangan tersebut. Kompetensi sumber daya manusia tidak memoderasi hubungan antara sistem pengendalian intern dan kualitas laporan keuangan Pemerintah Daerah Kabupaten Aceh Selatan. Kompetensi sumber daya manusia mampu memoderasi hubungan Pemanfaatan Teknologi Informasi terhadap Kualitas Laporan Keuangan Pemerintah Daerah Kabupaten Aceh Selatan.